Assessment of musculoskeletal system in women with jumping mechanography - Yannis Dionyssiotis; Antonios Galanos; Georgios Michas; et al (Dove Medical Press, 2009)
Yannis Dionyssiotis1,2, Antonios Galanos1, Georgios Michas1, Georgios Trovas1, Georgios P Lyritis11Laboratory for Research of the Musculoskeletal System, University of Athens, KAT Hospital, Kifissia, Greece; 2Rehabilitation Department, Rhodes General Hospital, Rhodes, GreeceAbstract: The purpose of this study was to investigate and add reference data about the musculoskeletal system in women. The mechanography system of the Leonardo™ platform (Novotec, Germany) was used to measure parameters of movement (velocity, force, power) in 176 healthy Greek women aged 20–79 years, separated according to age decade in six groups: group 1 (n = 12), 20–29 years; group 2 (n = 14), 30–39 years; group 3 (n = 33), 40–49 years; group 4 (n = 59), 50–59 years including 21 postmenopausal; group 5 (n = 31), 60–69 years including 12 postmenopausal; and group 6 (n = 27), 70–79 years all postmenopausal. This system measures forces applied to the plate over time, calculates through acceleration the vertical velocity of center of gravity and using force and velocity it calculates power of vertical movements. All women performed a counter-movement jump (brief squat before the jump) with freely moving arms. Weight was recorded on the platform before the jump and height was measured with a wall-mounted ruler. Body weight and body mass index were gradually increased; on the contrary height and all movement parameters except force (velocity, power) were statistically decreased during aging and after menopause.Keywords: biomechanics, ground reaction force, power, women, menopause